Simulasi Monte Carlo dalam Memprediksi Tingkat Pendapatan Advertising - Beni Mulyana Putra (SAFE-Network, 2020)
Fulfilling consumer needs is the goal of every business. Owned business capital will affect the readiness to serve consumer demand. The purpose of this study is to predict the level of advertising revenue at Vand Advertising Printing in order to facilitate business owners in preparing business strategies quickly and optimally. This research data is income data from January 2017 to December 2019 which is modeled using the Monte Carlo method. Income level prediction will be carried out annually. Based on the results of the tests that have been done, it is found that the system used to predict the level of advertising revenue with an average accuracy of 90%. The high level of accuracy means that the application of the Monte Carlo method is considered able to predict the level of advertising revenue each year. So that it can make it easier for business owners to choose the right business strategy to increase advertising revenue.